A importância da função afim e da Geometria Plana no aprendizado de Física do Ensino Médio e o GeoGebra como ferramenta fundamental - COSTA, André Gustavo Cruz da (2018)
Mathematics is the foundation of many studies; one in particular is Elementary School Mathematics, which has always been the base of countless paths chosen by teachers and professors. In engineering, it is impossible to understand the depth of Calculus without some basic knowledge of Elementary School Mathematics and statistics is part of most university syllabus. Is that a way to use the vast forms of Statics before mastering simple algebra concepts from basic Mathematics? Even in Law, speciﬁcally in succession and social security law, the Rule of Three or fractions are widely used. Obviously, not knowing basic Mathematics aﬀects more than just the studies after elementary school, it also aﬀects something in parallel, high school Physics, for example. Most of the problems proposed in Physics textbooks bring mathematical calculations, for which, without it, one can never reach the always-sought answer. The present study relates the importance between the polynomial function in Physics learning movements, and the Uniform Rectilinear Motion (URM), it also demonstrates the application of Flat Geometry in the study of Geometric Optics. Finally, it proposes uses for the GeoGebra application in the construction of graphs for computer labs and in the creation of animation and dynamic activities. Not only does such uses foster students’ interest in Physics, but also facilitates the resolution of function exercises and Geometry. GeoGebra has many versions and the one used in the present study is GeoGebra Classic 6.